Quality and performance of validated prognostic models for survival after resection of intrahepatic cholangiocarcinoma: a systematic review and meta-analysis. Issue 1 (January 2021) - Büttner, Stefan; Galjart, Boris; Beumer, Berend R.; van Vugt, Jeroen L.A.; van Eijck, Casper H.J.; Polak, Wojciech G.; de Jonge, Jeroen; Homs, Marjolein Y.V.; van Driel, Lydi M.J.W.; Pawlik, Timothy M.; Steyerberg, Ewout W.; Ijzermans, Jan N.M.; et al.
Abstract: Background: The objective of this systematic review was to evaluate the performance of prognostic survival models for intrahepatic cholangiocarcinoma (iCCA) when validated in an external dataset. Furthermore, it sought to identify common prognostic factors across models, and assess methodological quality of the studies in which the models were developed. Methods: The PRISMA guidelines were followed. External validation studies of prognostic models for patients with iCCA were searched in 5 databases. Model performance was assessed by discrimination and calibration. Results: Thirteen external validation studies were identified, validating 18 different prognostic models. The Wang model was the sole model with good performance (C-index above 0.70) for overall survival. This model incorporated tumor size and number, lymph node metastasis, direct invasion into surrounding tissue, vascular invasion, Carbohydrate antigen (CA) 19-9, and carcinoembryonic antigen (CEA). Methodological quality was poor in 11/12 statistical models. The Wang model had the highest score with 13 out of 17 points. Conclusion: The Wang model for prognosis after resection of iCCA has good quality and good performance at external validation, while most prognostic models for iCCA have been developed with poor methodological quality and show poor performance at external validation.